Role of compensating Li/Fe incorporation in Cu0.945Fe0.055−xLixO: structural, vibrational and magnetic properties. Issue 51 (22nd June 2017) - Nasir, Mohd.; Patra, N.; Ahmed, Md. A.; Shukla, D. K.; Kumar, Sunil; Bhattacharya, D.; Prajapat, C. L.; Phase, D. M.; Jha, S. N.; Biring, Sajal; Sen, Somaditya
Abstract : Monoclinic single phase Cu0.945 Fe0.055− x Li x O, with Cu 2+ properly substituted by Fe 3+ and Li 1+, shows enhanced magnetic moment with stronger FM coupling due to Li 1+ doping. Abstract : Doped transition metal oxides, like CuO, are spintronic materials. An increase of magnetic moment has been reported in Fe-doped CuO. 1 Additional secondary doping elements such as Li may further modify magnetism in transition metal oxides 2, 3 due to changes in valence state and size. Such complex doping may generate secondary impurity phases, restricting the success of such applications. Enhancement of magnetic properties strengthens applicability of the materials in devices. Single phase monoclinic Cu0.945 Fe0.055− x Li x O crystalline powders without any impurity are synthesized. Structural studies, electronic valence state, fine structure, and local geometry of constituent elements confirm the purity of the materials and provide clues to probable reasons leading to enhanced magnetism. Ferromagnetic coupling between neighboring spins is most likely dependent on the spin and separation between the spin species.